Sidartha Gautama - Heru Syahputra; Aldia Suriadi; Dtm. Mhd. Imam Alhaq; Muhammad Andry Al Alif Nasution (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Siddhartha Gautama is a central figure in the spiritual and philosophical history of the world, known as the Buddha, the founder of Buddhism. The background of this study stems from a reflection on life, suffering, and the search for the meaning of human existence, as experienced by Siddhartha prior to his enlightenment. This paper addresses the issue of how Siddhartha Gautama's spiritual journey shaped the core teachings of Buddhism, particularly within the context of the Four Noble Truths. The objective of this research is to philosophically examine Siddhartha Gautama’s existential transformation and the relevance of his teachings to modern understandings of suffering and happiness. The method used is a qualitative-descriptive study with a historical-philosophical approach, based on literature review of classical texts and contemporary interpretations. The conclusion shows that Siddhartha Gautama’s path to enlightenment illustrates a liberation process from suffering through deep understanding of the Four Noble Truths.